Improvement of Chitinase Production from a Newly Isolated Chitinolyticbacter meiyuanensis SYBC-H1 Using Central Composite Design Technique - Hao, Zhi-Kui; Cai, Yu-Jie; Liao, Xiang-Ru; Ge, Xiang-Yang; Zhang, Hai-Rong; Gao, Fei (Asian Journal of Chemistry, 2011)
The effect of physical processes such as rpm of the shaking incubator, initial pH of the medium and temperature on the production of chitinase from a newly isolated Chitinolyticbacter meiyuanensis SYBC-H1 was studied using central composite design technique. The individual optimum levels of rpm of the shaking incubator, initial pH of the medium and temperature were found to be 233 rpm, 6.44 and 26.21 ºC, respectively for chitinase production. As a result, maximum chitinase activity of 5.20 U/mL was obtained in the optimized medium, which was 15.5-fold higher than that in the basal medium.